Pemanfaatan Tumbuhan di Lingkungan Sekolah Sebagai Media Alami pada Materi Keanekaragaman Tumbuhan di SMA dan MA Kecamatan Montasik - Eriawati Eriawati (Universitas Islam Negeri Ar-Raniry, 2016)
Utilization of the learning environment in biology canprovidedirect learning experiences to the students by observing natural phenomena in accordance with the material being studied, which is expected to create the conditions that can develop students' interest and motivation to be active in the learning process. This study aims to fine out the students improvement and students learning activities by using plants in the school environment as a natural medium to the concept of plant diversity in SMA and MA at districts Montasik. The research was conducted at several SMA and MA at districts Montasik. The population and samples in this study was SMA and MA at districts Montasik. The data were collected by using test and observation. The hypothesis was tested by using t-test. The data obtained tcount was 16.94. ttable was 2.086, thus tcount ï€¾ttable or 16.94 ï€¾ 2.086. So Ho is rejected, while Ha is accepted. Showed that means the use of plants in the environment of the school as a natural medium on the material plant diversity can improve student learning outcomes. From the results of observation of students learning activity, it can be seen that the use of the school environment as a natural media can enhance students' learning activities.